2002
DOI: 10.1002/esp.402
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rock moisture on Schmidt hammer rebound: tests on rock samples from Marion Island and South Africa

Abstract: In an assessment of the influence of internal rock moisture content on Schmidt hammer readings, rebound (R) values are found to decrease with increasing moisture content. For samples of basalt, sandstone and dolerite the maximum decrease in R-values is found between oven dry values and saturated rock rebound values, the magnitude of which varies from 2 to 10 points on the R-scale. A quartzite block has the greatest decline of 6 points at 60 per cent saturation. For certain rock types under differing site-to-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 13 publications
2
56
1
1
Order By: Relevance
“…allow for any movements of the rock upon impact of the Schmidt hammer, which might result in inconsistency of R−values (Sumner and Nel 2002). Silt or single grains of fine sand, if found on the analyzed surface, were re− moved, and micro−roughness was measured in three smoothest lichen−free spots (thirty measurements per test site) parallel to striation in order to omit visible mi− cro−erosional features on the run of the profilometer (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…allow for any movements of the rock upon impact of the Schmidt hammer, which might result in inconsistency of R−values (Sumner and Nel 2002). Silt or single grains of fine sand, if found on the analyzed surface, were re− moved, and micro−roughness was measured in three smoothest lichen−free spots (thirty measurements per test site) parallel to striation in order to omit visible mi− cro−erosional features on the run of the profilometer (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The block mass of the rock to be tested is signifi cant, and the test cannot be used on small, light blocks. Sumner and Nel (2002) suggest that block weight should exceed 25 kg for accurate and consistent rebound determinations, whilst Demirdag et al (2009) have found experimentally that cubic blocks should have at least 11 cm edges. Finally, there may be between-hammer variation and deterioration of hammer performance with age.…”
Section: The Classic Schmidt Hammermentioning
confidence: 97%
“…This may present particular problems for the testing of heritage structures and surfaces such as rock art panels. The test is sensitive to moisture contents, especially in weak rocks (Sumner and Nel, 2002). The block mass of the rock to be tested is signifi cant, and the test cannot be used on small, light blocks.…”
Section: The Classic Schmidt Hammermentioning
confidence: 99%
“…Measurements recording an R value of <10 were assigned the value 9. In order to minimise the influence of technique error, the precautions outlined by Day and Goudie (1977), Day (1980), McCarroll (1987, 1989 and Sumner and Nel (2002) were adhered to and a sampling strategy was adopted following that of Anderson et al (1998).…”
Section: Schmidt Hammermentioning
confidence: 99%